Aquepts in South Mahanadi Delta of Odisha: Characteristics and Land Use Interpretation - Mishra, K. N.; Jena, D.; Samanta, T. K. (International Journal of Bio-resource and Stress Management, 2016)
The floodplain soils of South Mahanadi delta are dominantly Aquepts with characteristics associated with wetness. Four representative pedons of these Aquepts in a transect under South Mahanadi delta of Odisha were characterized and classified for land use interpretation. The soils are deep and the matrix colour are dominantly gray with hue of 2.5Y, 2.5YR, 10YR, value of 3 to 5 and chroma of 2 or less in most of the horizons with mottles and exhibited redoximorphic features like gleying, high chroma mottles and Fe-Mn concretions. Wide variation in sand/silt ratio (>0.2) and uniformity value (>0.6) in these soils indicated lithological discontinuity. The distribution of free Fe2O3 showing positive correlation with clay contents (r=0.59**) indicate that gleying extends deeper down the profiles. The soils are well saturated with bases (61 to 91%) and the CEC/clay ratio of the soils (47–81%) indicates that the soils belong to a mixed mineralogy family class. The soils are classified as Epiaquepts and Endoaquepts at great group levels. Alternate land use plans developed through soil site suitability for Epiaquepts are transplanted rice in kharif and maize/tomato/pulses in rabi season. The Endoaquepts can be used to grow deep water rice in kharif/ followed by pulses in rabi season. Dugout farm pond and deep drainage channels may be viable options in these low lying Endoauepts for drainage of excess water from the surface and subsurface soils.